QUALITATIVE STUDY ON RELIGIOUS EDUCATION AND TOLERANCE AS A KEY FOR SOCIAL DEVELOPMENT - Dr. Seema Manzoor,; Manzoor, Dr. Asma; Idrees, Dr. Nusrat (Journal of Peace, Development and Communication, 2022)
Varied characteristics and elements combine together to form social structure of our society, which is why it is unique in nature and as a result, every human tend to be unique and individual personality. These human attributes becomes the foundation of the society and moral and ethical values are based on tolerance, harmony, peace, loyalty and sincerity. Among all these traits tolerance is of prime importance and due to globalization it has gained more significance. People from different communities follow different religion and due to diversity of culture they have different life-style, but still they share common social and economic scenario, which helps in forming tolerance oriented society. All religions promote peace, tolerance and harmony as a key to equitable society. Every individual has the right to enjoy his freedom to live by his/her choice and freedom to worship. Basically this freedom leads to a society with less conflicts and war. Islam has always taught us to have religious freedom in the context of peace and tolerance. In Quran, 256th Ayah of Surah Al-Baqrah clearly states that “There shall be no compulsion in [acceptance of] the religion. The right course has become clear from the wrong”. Islam emphasizes on practicing rather than praising Islamic teachings. The main purpose of this study is to examine how human societies have evolved according to these social attributes. Qualitative research method was chosen to conduct in-depth study through content analysis by using library research method. According to the qualitative analysis it has been concluded that today world is focusing on religious tolerance and promotion of pluralistic society. This is a very practical approach to avoid religious conflicts and to develop a peaceful society for social development. The study also focuses on consequences of religious intolerance and its consequences. The social development can be achieved by social awareness and enlightenment and by reforming the ethical and moral values to treat every individual as an important and productive part of the society.